Pengaruh Potongan Harga dan Kemudahan Penggunaan Terhadap Keputusan Penggunaan E-Wallet Shopee Pay - Risha Fatikha Sari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
At this time technology is developing rapidly, this also triggers changes in human lifestyles as consumers. One of them is a cashless payment technique using an electronic wallet (e-wallet). The research entitled